Determinants of early marriage among married women in Injibara town, north West Ethiopia: community-based cross-sectional study - Minale Bezie; Dagne Addisu (BMC, 2019)
Abstract Background Early marriage is occurred when one or both of the spouses are below the age of 18 years at the time of their first marriage. It is one of the major traditional practices in developing counties particularly in Ethiopia; which has significant physical, intellectual, psychological and emotional effects and reduces educational opportunities and the chance for personal growth for both boys and girls. Even though this traditional practice was the common cultural events in the study area, there is no prior study on the magnitude and its determinant factors. Hence, the study was aimed to determine the prevalence and determinant factors of early marriage among married women in Injibara town, North West Ethiopia. Methods A Community-based cross-sectional study was conducted from September to December 2018. A total of 373 women were included in the study. A multistage sampling procedure was applied to select the study participants. Data analysis was done by using SPSS versions 23. Both descriptive & analytical statistics were computed. Statistical significance was considered at P < 0.05 and the strength of association were assessed by using adjusted odds ratio with 95% confidence interval. Result The prevalence of early marriage was 167(44.8%). The minimum and maximum ages at first marriage were 9 and 23 years respectively. Non-formal educational level of the father [Adjusted Odd Ratio (AOR) =2.32; 95%CI = 1.33-4.05], family's average monthly income <1000 Ethiopian birr [AOR = 2.32, 95%CI = 1.27-4.24], family size ≥7 [AOR = 3.59, 95%CI = 1.94-6.63] and non-formal education level of the respondents [AOR = 5.16; 95%CI = 2.87-9.28] were found to be associated with early marriage. Conclusion The prevalence of early marriage was high in Injibara town, Ethiopia. Factors that tend to facilitate early marriage in this town include family income, family size, educational level of the father and that of the respondent. Improving on the strategies that promote formal education will reduce the level of early marriage in Injibara town, Ethiopia.